lmplementasi Desain Fasilitas Kerja Ergonomis Untuk Menurunkan Resiko Pada Postur Kerja Duduk Statis - Purnama, Ign. Luddy Indra; Dewi, Luciana Triani; Yuniartha, Deny Ratna (Jurnal Rekayasa Sistem Industri, 2015)
A staticwork position with sitting is common work posture founded in industry, particularly small industryin Indonesia. The problem that review in this paper is the activity of workers sitting static for processingemping in Yogyakarta. Activity done by means sitting on the floor without using table. The activity carriedin a continuous long term, so as to cause disease risks muscle and bone especially lower back. Ergonomic workfacilities is implemented to solve the work problem with table and chair. The design of work table is developedwith concept low cost improvement and consider with secure, health, and convenience of worker. The designprocess using participatory approach by involving worker to get best design. The result of facilities implementationcan be achieved a decrease ih the risk of work. The potential risk of work posture can be repair thatshown of the RULA score from 6 to 4, and no more complain the back and waist from worker activity.